A Platform Programming Paradigm for Heterogeneous Systems Integration - Gemlau, Kai-Bjorn; Kohler, Leonie; Ernst, Rolf (Proceedings of the IEEE, 2021)
To cope with growing computing performance requirements, cyber-physical systems architectures are moving toward heterogeneous high-performance computer architectures and networks. Such architectures, however, incur intricate side effects that challenge traditional software design and integration. The programming paradigm can take a key role in mastering software design, as experience in automotive design demonstrates. To cope with the integration challenge, this industry has started introducing a programming paradigm that efficiently preserves application data flow under platform integration and changes with minimum performance loss. This article will revisit this paradigm that is currently used for lock-free multicore programming and explain its extension to the system level. It will then explore its application to two important developments in industrial design. This article will conclude with an evaluation of its properties, its overhead, and its application toward a robust design process.